Limit analysis of an elastic thin oscillating layer - Jamal Messaho; Abdelaziz Ait Moussa (Boletim da Sociedade Paranaense de Matemática, 2016)
The aim of this paper, is to study the limit behavior of the solution of a convex elasticity problem with negative power type, of a containing structure, an elastic thin oscillating layer of thickness depending of a small enough parameter. The epi-convergence method is considered to nd the limit problems with interface conditions.